2007
DOI: 10.1007/s00128-007-9307-3
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Effect of Storage of Advanced Treated Water in a Building’s Plumbing System on Trihalomethane Levels

Abstract: Variations in trihalomethane (THM) levels during two-day period in the advanced treated water which had passed through a building's plumbing system (stored water) were compared with those in the advanced treated water delivered directly by the distribution system. THM levels in both the water were relatively uniform. The water quality deterioration measured by the increased THMs was apparently observed during the storage of the water in the plumbing system, even though the advanced treatment could produce high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…The summer season produced the greatest variations in concentration among the parameters (e.g., summer cold water age was over 200 h). This is supported with other studies showing warmer climates increased microbial growth (Zlatanović et al, 2017), TTHM formation (Yamamoto et al, 2007), metal leaching (NRC, 2006), and the loss of disinfectant residual (Nguyen et al, 2012). The current study focuses on cases that can generate useful predictions regarding the impact of operational and design changes on water age, and therefore drinking water quality.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The summer season produced the greatest variations in concentration among the parameters (e.g., summer cold water age was over 200 h). This is supported with other studies showing warmer climates increased microbial growth (Zlatanović et al, 2017), TTHM formation (Yamamoto et al, 2007), metal leaching (NRC, 2006), and the loss of disinfectant residual (Nguyen et al, 2012). The current study focuses on cases that can generate useful predictions regarding the impact of operational and design changes on water age, and therefore drinking water quality.…”
Section: Resultssupporting
confidence: 85%
“…Constants used for plumbing modeling should be an area of future research. It is known that higher temperatures from seasonal changes result in increase in microbial concentrations, TTHM formation (Yamamoto et al, 2007), and a greater chlorine reaction rate (Courtis et al, 2009). Also, higher pH is known to increase TTHM formation (Liang & Singer, 2003) and decreases effectiveness of chlorine disinfection (Ward et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…49−51 THM formation occurs in pipes, but substantial formation appears to be associated with free chlorine systems. 4,52,53 Another study reported higher levels of THMs in buildings up to 89% higher than the levels found at the service line. 52 However, in the chloramine system considered here, the effects of residence in the building plumbing system appear to be relatively modest and somewhat beneficial (as HAAs are degraded).…”
Section: Influence Of Building Plumbing Design and Operational Parame...mentioning
confidence: 97%
“…For the determination of residual chlorine (CLres), the DPD (N, N-diethyl-p-phenyl phenylene diamine) colorimetric method for low concentrations (0.0 to 2.0 mg/L) was used [23] [27].…”
Section: Water Analysismentioning
confidence: 99%